Neutropenic Fever in a Two-and-a-Half Month Old Girl: Severe Congenital Neutropenia - Hüseyin Gülen; Merve Öçalan; Ayşen Türedi Yıldırım; F. Sırrı Çam; Hamide Betül Gerik Çelebi (Galenos Yayinevi, 2018)
Severe congenital neutropenia is a hereditary disease characterized by a low number of neutrophils occurring from the first months of life leading to severe infections. It is rare but threatens life because of severe infections. For this reason, early diagnosis and treatment of this disease is important. Here, we present a case of a two and a half month old girl who was admitted to our clinic with fever and absolute neutropenia was determined in her clinical course.